Impact of Pharmaceutical Intervention on Inhalation Technique - Ansari, Mukhtar; Rao, B.S.; Koju, Rajendra; Shakya, Rajani (Kathmandu University Journal of Science, Engineering and Technology, 2005)
The study carried out presents causes of poor compliance among the patients using inhaler devices. Evaluation of the patient's prior knowledge and practice of using inhalers and the improvement on using inhalers after counseling intervention through standard guidelines were the outcome measures of this study. It was hypothesized that pharmaceutical intervention gives better outcome. There was lesser compliance and lesser improvement in inhalation technique score in females than in males and furthermore the female patients falling under the resting category were mostly above the age of 60 years. Comparing the mean scores and mean improvement before and after counseling in rotahaler users, it was observed that there was 62.25% improvement in discharged patients 57.75% improvement in outpatients after counseling 47.87% improvement in inpatients after first counseling 80.12% improvement after second counseling. In the case of MDI users, there was 63.30% improvement after counseling. From the follow-up (second counseling) in inpatients it was evident that as the number of counseling was increased, there was an increase in improvement in mean score, decrease in numbers of critical point missing, increase in compliance of patients to inhalation techniques and ultimately there were better outcomes.